Syeikh Nyass and The Making of Sacred Narratives: Myth, Reincarnation and Sūfi Identity in Nigeria - Babangida, Muhammad Gidado; Ali, Samaila (DINIKA : Academic Journal of Islamic Studies, 2025)
This study examines the theological and social perception of Nigerian Sūfis (mystics) regarding the claims of Syeikh Nyass's reincarnation and its significance or otherwise for Sūfi practice. It uses a conceptual tool known as the Myth and Reality Framework developed by Karl Popper to distinguish between theological realities and mystical beliefs. The study adopts a Qualitative research method by employing both primary and secondary sources of data collection, ranging from interviews, review of published Scholarly works, and Sūfi literature, to investigate the basis of reincarnation within the Sūfi tradition and how Nigerian Sūfis responded to the claim of its actualization vis-à-vis Syeikh Nyass. The study found that Syeikh Nyass has been one of the most influential Sūfi figures whose influence spread across West Africa, particularly Nigeria. Nevertheless, Nigerian Sūfis remarkably divided regarding Nyass’s alleged reincarnation; while some adherents affirm its occurrence claiming that the spiritual power of Syeikh Nyass continues even after his death through his chosen followers, enabling them to perceive his physical presence, while others vehemently reject such possibility, arguing that it is against the tenets of Islam. The study concludes that Subsequent studies may examine the existence of this spiritual reincarnation across Sūfi Orders such as Qadiriyya, Naqsybandiyya, and Chisytiyya to compare their theological perception and socio-cultural implications.